Rock Mechanical Approaches for Predicting Fault Behaviour During CO2 Injection. (July 2017) - Tenthorey, Eric; Richard, Thomas; Dewhurst, David
Abstract: This paper presents the pre-injection fault characterisation that has been conducted at the CO2CRC Otway Project in Victoria, Australia, aimed at understanding the response of faults to pressure increases in the formation, fault transmissibility horizontally and vertically, and also presents a methodology to extract key rheological fault properties using novel rock mechanical techniques. The initial modelling results show that the likelihood of injection induced fault reactivation is exceedingly small, due to the very small pressure increases associated with injection (∼ 0.05 MPa after about 100 days of injection during the Stage 2C experiment). The potential for CO2 flow across the main reservoir-cutting faults was quantified using the shale gouge ratio algorithm. Results indicate that the faults should be sealing to some degree and should therefore restrict the lateral movement of CO2 . Despite these positive results with regard to fault behaviour during current operations, there remains significant uncertainty with regard to certain fault properties such as friction and cohesion that have a large effect on fault stability. Here we develop a workflow which involves several rock mechanical testing techniques to gain information regarding a key fault at the Otway site. One relatively novel technique that is used is the scratch test, which measures strength heterogeneity of the host rock at the centimetre scale. The scratch data can be correlated to certain well logs via a multivariate analysis in order to develop proxies for rock strength that can be applied to other wells and also to wells that traverse fault zones, thereby providing some estimate of fault strength. This scratch analysis is complemented by a series of triaxial experiments designed to measure poroelastic properties and also assess the rate and state frictional parameters of potential fault gouge materials. While the work presented here is aimed specifically at understanding the properties of key faults at the Otway Project, it is hoped that the knowledge gained and the transforms developed here can be used as a guide to constrain fault properties at other CCS sites.